‘A Touch of Love’ - Norhidayah, Mohamad (2017)
‘A Touch of Love’ is a program organized by Universiti Malaysia Pahang and Perbadanan Kemajuan Pertanian Negeri Pahang (PKPP) to cherish and celebrate 167 orphans from Nur Iman Orphanage and Tun Abdul Razak Caring House. These orphans were entertained with activities and games to fill up their time and later they were taken to Safari Park Bukit Gambang Resort City Kuantan.